Nervous System Deletion of Mammalian INDY in Mice Mimics Dietary Restriction-Induced Memory Enhancement. (18th August 2020) - Fan, Shou-Zen; Sung, Chih-Wei; Tsai, Yi-Hsuan; Yeh, Sheng-Rong; Lin, Wei-Sheng; Wang, Pei-Yu
Abstract: Reduced expression of the Indy ( I'm Not Dead Yet ) gene extends life span in Caenorhabditis elegans and Drosophila melanogaster and improves the metabolic heath of Mus musculus through inducing a physiological status akin to dietary restriction (DR). Although the function of Indy in aging and hepatic metabolism has been extensively studied, its role in the mouse nervous system remains unclear. Here, we explore the effect of mammalian Indy ( mIndy, SLC13A5) gene deletion on murine cognitive function. Similar to what is seen in DR animals, systemic deletion of the mIndy gene ( mIndy knockout [KO]) significantly improves memory performance and motor coordination of mice. Both DR and mIndy KO mice act normally in other behavioral tasks, including emotional, social, and food-seeking behaviors. Moreover, we find that tissue-specific deletion of mIndy in the nervous system is sufficient to improve memory performance, while liver-specific deletion has no effect on memory, and results in tests of motor coordination show no changes in either mutant. Mice with systemic or nervous system deletion of mIndy also exhibit increased hippocampal neurogenesis and dendritic spine formation in dentate granule cells; these changes are well-documented contributors to enhanced memory performance. Together, our studies demonstrate a critical role for brain-derived mIndy expression in the regulation of memory function in animals.